Novel GIRlncRNA Signature for Predicting the Clinical Outcome and Therapeutic Response in NSCLC - Zhang, Qiangzhe; Liu, Xicheng; Chen, Zhinan; Zhang, Sihe (Frontiers in Pharmacology, 2022)
Background: Non-small cell lung cancer (NSCLC) is highly malignant with driver somatic mutations and genomic instability. Long non-coding RNAs (lncRNAs) play a vital role in regulating these two aspects. However, the identification of somatic mutation-derived, genomic instability-related lncRNAs (GIRlncRNAs) and their clinical significance in NSCLC remains largely unexplored. Methods: Clinical information, gene mutation and lncRNA expression data were extracted from TCGA database. GIRlncRNAs were screened by a mutator hypothesis-derived computational frame. Co-expression, GO and KEGG enrichment analyses were performed to investigate the biological functions. Cox and LASSO regression analyses were performed to create a prognostic risk model based on the GIRlncRNA signature (GIRlncSig). The prediction efficiency of the model was evaluated by using correlation analyses with mutation, driver gene, immune microenvironment contexture, and therapeutic response. Prognostic performance of the model was evaluated by external datasets. A nomogram was established and validated in the testing set and TCGA dataset. Results: 1446 GIRlncRNAs were selected from the screen, and the established GIRlncSig was used to classify patients into high and low-risk groups. Enrichment analyses showed that GIRlncRNAs were mainly associated with nucleic acid metabolic and DNA damage repair pathways. Cox analyses further identified nineteen GIRlncRNAs to construct a GIRlncSig-based risk score model. According to Cox regression and stratification analyses, fourteen prognostic lncRNAs (AC023824.3, AC013287.1, AP000829.1, LINC01611, AC097451.1, AC025419.1, AC079949.2, LINC01600, AC004862.1, AC021594.1, MYRF-AS1, LINC02434, LINC02412, and LINC00337) and five protective lncRNAs (LINC01067, AC012645.1, AL512604.3, AC008278.2, and AC089998.1) were powerful predictors. Analyses of the model showed that these GIRlncRNAs were correlated with somatic mutation pattern, immune microenvironment infiltration, immunotherapeutic response, drug sensitivity and survival of NSCLC patients. The GIRlncSig risk score model demonstrated good predictive performance (AUCs of ROC for 10-year survival was 0.69) and prognostic value in different NSCLC datasets. The nomogram comprising GIRlncSig and tumor stage exhibited improved robustness and feasibility for predicting NSCLC prognosis. Conclusion: The newly identified GIRlncRNAs are powerful biomarkers for clinical outcome and prognosis of NSCLC. Our study highlights that the GIRlncSig-based score model may be a useful tool for risk stratification and management of NSCLC patients, which deserves further evaluation in future prospective studies.